Emprego de técnicas avançadas em estudos bioeletroquímicos de substâncias de interesse biológico - Ferreira, Fabrícia da Rocha (2013)
In the present study, compounds derived from β-lapachone were electrochemically studied in protic (phosphate and acetate buffer) and aprotic (DMF + TBAP) media, using glassy carbon as working electrode. The electroreducedintermediatesof the quinones reacted with oxygen, indicative of the generation of reactive oxygen species. The interaction of the quinones β-lapachone, α-lapachone and nor-β-lapachone with DNA, was investigated using the technique of quartz crystal microbalance.To increase the solubility of the quinones, in order to allow in vivo studies, the formation of inclusion complexes with β-cyclodextrin was evaluated. Positive results were obtained, leading to a viable formulation alternative for further biological studies with the compounds. β-lapachone was studied spectroelectrochemically through the techniques of Polarization Modulation Infrared Reflection Absorption Spectroscopy + Cyclic Voltammetry to confirm the formation of the hydrogen bondfrom the electroreduced β-lapachone and the secondary hydroxy group of β-cyclodextrin. The inclusion complex betweenmangiferin, an antioxidant polyphenoland β-cyclodextrin, was confirmed using the techniques of Fourier Transform Infrared Spectroscopy, Hydrogen Nuclear Magnetic Resonance, Differential Scanning Calorimetry and Polarization Modulation Infrared Reflection Absorption Spectroscopy. Also, the increase of the antioxidant activity of mangiferin was demonstrated when in presence of β-cyclodextrin, by means of radical scavenging activity toward 2,2’-diphenyl-1-picrylhydrazyl radical (RSA-DPPH ), with additional analysis of solvent effects, being demonstrated that below 50% of organic solvent, it is impossible to work with this method. The assay of the capacity of oxygen radical absorbance capacity-fluorescein (ORAC-FL) was also used, showing that the complex mangiferin: β-cyclodextrin is fifteenfold more potent than the standard molecule,Trolox. Using Electrophoresis and Differential Pulse Voltammetry, it was possible to emphasize that the method used by our research group for the ssDNA production (treatment acid-base with heating) is useful, simple, cheap and completely reproducible, being this, one of the methods used to show the interaction between DNA and free or complexed thymol with cyclodextrin. This interaction was still evaluated using dsDNA biosensor through Differential Pulse Voltammetry, Electrochemistry Quartz Crystal Microbalance and Scanning Electrochemistry Microscopy.